Penanaman Mangrove di Pantai Pondok Asem Dengan Tema Gaya Hidup Berkelanjutan - Masrukin; Lukman Haki; Khoirul Anam, Muhamad; Muhammad Zainal Roisul Amin (Fakultas Teknik, Universitas PGRI Banyuwangi, 2023)
The implementation of the Pancasila Student Profile is one of the efforts that can improve the quality of education in Indonesia. To improve the profile values of students of SMKN Darul Ulum Muncar, efforts to strengthen student profiles by planting mangroves at Pondok Asem Beach, Tegaldlimo District. The mangrove planting carried out will increase concern for the surrounding environment and students will learn to know how important it is to maintain natural resources. Mangrove planting is carried out by perhutani and students of SMKN Darul Ulum Muncar. The results of the activity can foster the enthusiasm of students to maintain the coastal ecosystem.